GUI for conic sections: parabola, ellipse and hyperbola - Gul, Saima; Tufail, Muhammad Yousuf (Revista Mexicana de Física E, 2024)
In this paper we provide three Excel spreadsheets for the explanation of Parabola, Ellipse and Hyperbola respectively. Our target audience is University science students (Physics/Mathematics/Computer science) and mentors.